Streptomyces sp. strain MUSC 5 from mangrove forest in Malaysia: Identification, antioxidant potential and chemical profiling of its methanolic extract - Hefa Mangzira Kemung; Loh Teng-Hern Tan; Kok-Gan Chan; Hooi-Leng Ser; Jodi Woan-Fei Law; Bey Hing Goh (Progress in Microbes and Molecular Biology)
The present study explored the antioxidant potential of a Streptomyces sp. strain MUSC 5 from the mangrove forest soil in the Pahang State, Peninsular of Malaysia and determined the presence of biologically active chemical constituents contained in the methanolic extract. The 16S rRNA genomic DNA extraction, phylogenetic analysis and phenotyping methods were used to confirm identity of strain. The antioxidant potential of methanolic extract from Streptomyces sp. strain MUSC 5 was assessed using a number of antioxidants assays which included free radical scavenging assays, metal chelation and ferric reduction antioxidant power (FRAP) assay. Furthermore, Gas chromatography Mass Spectrometry (GC-MS) was used to determine the presence of biologically active chemical compounds in methanolic extract of Streptomyces sp. strain MUSC 5. The strain was confirmed as belonging to Streptomyces genus. Antioxidant studies of the methanolic extract from Streptomyces sp. strain MUSC 5 revealed antioxidant activity of 24.97 ± 0.99 %, 22.95 ± 3.21% and 26.81 ± 1.05% against free radicals ABTS, DPPH and metal chelation, respectively. The result of FRAP assay was expressed in dose of 1-2 mg which was equivalent to 1.73- 2.15 microgram (μg) of ascorbic acid. GC-MS analysis carried out on the methanolic extract of Streptomyces sp. strain MUSC 5 detected the presence of 11 known compounds belonging to pyrrolopyrazine, esters, fatty acid esters, triterpene and an alkane group of compounds. The study supports the notion that Streptomyces from underexplored mangrove forest offer promising Streptomyces with antioxidant activity and could serve as important sources for new antioxidant agents.